Microsoft Office Project Server 2007 : the complete reference - Gochberg, Dave (McGraw Hill professional., 2008)
This is the ultimate guide to Microsoft Office Project Server 2007. This comprehensive guide takes you through the planning and implementation lifecycle of a Project Server installation. You will learn how to utilize this powerful software to set up and manage projects, allocate human as well as financial resources, track progress, and adjust activities quickly to accommodate project changes and updates.